Developing a risk score for early detection of bowel cancer using routine blood test data - Virdee, PS (2021)
Introduction Bowel cancer is the fourth most common type of cancer in the UK. Approximately 55% of patients are diagnosed with a late-stage tumour (Stage 3 and 4), where likelihood of survival is reduced: five-year survival is 93% at Stage 1 vs. 10% at stage 4. Early detection is crucial. The full blood count (FBC) blood test is commonly performed in primary care. It may help but currently there is limited evidence on how to utilise this test for early detection.